Vaccine Hesitancy Drives Low Human Papillomavirus Vaccination Coverage in Girls Attending Public Schools in South Africa - Khosa, Languta A.; Meyer, Johanna C.; Motshwane, Feni M. M.; Dochez, Carine; Burnett, Rosemary J. (Frontiers in Public Health, 2022)
Girls aged ≥9 years attending South African public sector schools are provided with free human papillomavirus (HPV) vaccination, through a schools-based programme. HPV vaccine misinformation spread via social media in 2014, was identified as a barrier to obtaining parental informed consent in some districts, including Sedibeng District, which subsequently had the lowest HPV vaccination coverage in Gauteng Province in 2018. This study investigated vaccine hesitancy in caregivers of girls in Grade 4-7 aged ≥9 years attending public schools in Sedibeng District. A cross-sectional survey using a self-administered questionnaire was conducted on caregivers of age-eligible girls attending all public schools in Sedibeng district with first dose HPV vaccination coverage of <70%. The questionnaire included demographics; HPV vaccination status of girls; reasons for not being vaccinated; and a 5 item tool measuring the determinants of vaccine hesitancy, using a 7-point Likert scale. Data were coded and captured on Microsoft Excel®. Except for collective responsibility which was reverse scored, the other 5C items (confidence, complacency, constraints, and calculation) were captured as follows: 1=strongly disagree, 2=moderately disagree, 3=slightly disagree, 4=neutral, 5=slightly agree, 6=moderately agree and 7=strongly agree. Descriptive and inferential statistical analyses were conducted using Epi InfoTM. Of the principals of all schools with <70% HPV vaccination coverage, 69.6% (32/46) gave permission. The response rate from caregivers of girls present on the day of data collection was 36.8% (1782/4838), with 67.1% (1196/1782) of respondents reporting that their daughters had received ≥1 dose of HPV vaccine. Only 63.1% (370/586) of respondents with unvaccinated daughters answered the question on reasons, with 49.2% (182/370) reporting reasons related to vaccine hesitancy. Statistically significant differences between caregivers of vaccinated and unvaccinated daughters were identified for four of the five determinants of vaccine hesitancy: confidence (vaccinated group higher), complacency (unvaccinated group higher), constraints (unvaccinated group higher) and collective responsibility (vaccinated group higher). This is the first South African study to (a) report results of the 5C scale, which was found to be very useful for predicting vaccination uptake; and (b) confirm that the relatively low HPV vaccination coverage in Sedibeng District is largely driven by reasons related to vaccine hesitancy.